Pengembangan Instrumen Penilaian Autentik Pada Materi Eksositem di SMA - Patongai, Dian Dwi Putri Ulan Sari; Saparuddin, Saparuddin; Palennari, Muhiddin (Universitas Negeri Makassar, 2020)
Abstract. This study aims to develop an authentic assessment instrument on ecosystem material for SMA using the 4D type development model (Define, Design, Develop, Disseminate) by Thiagarajan. The trial was carried out at SMA Negeri 1 Bulukumba in class X MIA 1. The results of expert validation showed that the project appraisal instrument, performance and lesson plans had a strong relevance with the value of V = 88%, 100% and 100% respectively where all three were greater than 75% that it fulfilled the content validity coefficient. The reliability test was carried out at the trial stage by analyzing the results of the teacher's assessment of students using developed instruments. The result of the reliability test shows the value of r11 = 0.943 or greater than 0.70 so that it can be stated that the instrument developed is valid and reliable.Keywords:Â development, authentic assessment, validation